Tipologii feminine în dramaturgia lui Romulus Guga - Cristina Rotaru (Revista de Istorie și Teorie Literară)
The analytical approach, focusing on the plays of Romulus Guga, aims to make a constructive distinction between the male and female discourse, not mainly for gender-specific reasons, but in order to identify a dramatic vision in which the female character plays the role of outlet for feelings of frustration, rebellion or obedience, that can be reproached not to feminine stances which became roles, but to the authorial consciousness. The identified typologies are designed archetypally and therefore I looked for their roots in theatrical solutions that stem from the Greek Antiquity, going through the Commedia Dell’arte and connect to the expressionist model of character development. Masks of the ego, female characters, all these are tuning forks that allow the voice deep down to take the shape of the word, designed as a poetic message and sent from the creator to the audience with whom it cohabitates in a moral ambiguity that is specific to the resolute time.